A Review Study of the Feasibility of Piezoelectric Fan Techniques for Cooling Electronic Components - Jasim, Haider F.; Ismael, Muneer A. (Basrah Journal for Engineering Sciences, 2024)
The electronic equipment industry has developed rapidly in recent years. The amount of heat emitted from such equipment is seriously increased. Increasing the temperature of the electronic devices degrades their performance and as a final result their failure. Therefore, the requirements for an effective cooling system have become more important than ever. One of the most important methods of heat dissipation that the researchers focused on is the use of piezoelectric fans (PE). The current study reviews most of the developments that have taken place since its discovery nearly 40 years ago and focused on reducing power consumption. Most of the improvements and developments have been focused on obtaining optimal designs for these piezoelectric fans, which are used in different applications. This review clarifies the foundations and concepts of designing piezoelectric fans by comparing the data presented in previous studies. Furthermore, in the last ten years, numerical simulation has entered as an effective tool in predicting the optimal design of piezoelectric fans. The design of piezoelectric fans is in two forms, either single or multiple. The single fan system is used within a limited range of applications, as large cooling systems cannot be replaced by it. Therefore, the cooling system consisting of multiple piezoelectric fans is promising as a unique solution to effectively dissipate heat in electronic devices. The percentage of experimental studies is about 32 % while the studies of CFD is about 21 %, and the combined one is about 47 %.